Circumferential Resection Margin Status as a Predictive Factor for Recurrence in Preoperative MRI for Advanced Lower Rectal Cancer Without Preoperative Therapy. Issue 1 (January 2021) - Mazaki, Junichi; Tsukamoto, Shunsuke; Miyake, Mototaka; Moritani, Konosuke; Sakamoto, Ryohei; Shida, Dai; Kanemitsu, Yukihide
Abstract : BACKGROUND: In Japan, total mesorectal excision plus lateral lymph node dissection without preoperative therapy is the standard treatment for advanced lower rectal cancer. Although long-term oncologic outcomes with preoperative therapy based on circumferential resection margin status in preoperative MRI has been reported, outcomes without preoperative therapy are unknown. OBJECTIVE: This study evaluated long-term oncologic outcomes of radical surgery without preoperative therapy in advanced lower rectal cancer based on circumferential resection margin status in preoperative MRI, with the aim of defining appropriate patient populations for preoperative therapy. DESIGN: This retrospective analysis compared long-term oncologic outcomes with preoperative MRI in patients with lower rectal cancer. SETTINGS: Patients were identified through a database managed by our institute. PATIENTS: In total, 338 patients with lower rectal cancer who underwent radical surgery between 2000 and 2014 at the National Cancer Center Hospital without preoperative therapy were included. MAIN OUTCOME MEASURES: The main outcome was relapse-free survival. RESULTS: The median follow-up period was 61.7 months (range, 3–153 months). Five-year relapse-free survival rates in MRI-predicted circumferential resection margin negative patients and positive patients were 76.0% and 55.6% ( p < 0.001). Univariate and multivariate analyses revealed pN stage (HR, 2.35; 95% CI, 1.470–3.770; p < 0.001), lymphatic invasion (HR, 2.03; 95% CI, 1.302–3.176; p = 0.002), venous invasion (HR, 2.15; 95% CI, 1.184–3.9; p = 0.01), surgical procedure (HR, 1.72; 95% CI, 1.115–2.665; p = 0.01), and MRI-predicted circumferential resection margin (HR, 1.850; 95% CI, 1.206–2.838; p = 0.0051) to be independent risk factors for postoperative recurrence. LIMITATIONS: This study was retrospective in design. CONCLUSIONS: Magnetic resonance imaging-predicted circumferential resection margin was associated with relapse-free survival without preoperative therapy, indicating its potential for use in selecting optimal preoperative therapy. See Video Abstract at http://links.lww.com/DCR/B335 . ESTADO DEL MARGEN DE RESECCIÓN CIRCUNFERENCIAL COMO FACTOR PREDICTIVO DE RECURRENCIA EN LA RESONANCIA MAGNÉTICA PREOPERATORIA, PARA EL CÁNCER RECTAL BAJO AVANZADO SIN TERAPIA PREOPERATORIA: ANTECEDENTES: En Japón, la escisión mesorrectal total con disección de ganglios linfáticos laterales y sin terapia preoperatoria, es el tratamiento estándar para el cáncer rectal bajo avanzado. Aunque se han reportado resultados oncológicos a largo plazo con terapia preoperatoria, basada en el estado del margen de resección circunferencial en la resonancia magnética preoperatoria, se desconocen los resultados sin terapia preoperatoria. OBJETIVO: Este estudio evaluó los resultados oncológicos a largo plazo de cirugía radical sin terapia preoperatoria, en cáncer rectal bajo avanzado, basado en el estado del margen de resección circunferencial en la resonancia magnética preoperatoria, con el objetivo de definir poblaciones de pacientes apropiadas para terapia preoperatoria. DISEÑO: Este análisis retrospectivo comparó los resultados oncológicos a largo plazo con resonancia magnética preoperatoria, en pacientes con cáncer rectal bajo. AJUSTES: Los pacientes fueron identificados a través de una base de datos administrada por nuestro instituto. PACIENTES: Se incluyeron un total de 338 pacientes con cáncer rectal bajo, que se sometieron a cirugía radical entre 2000 y 2014 en el Hospital Nacional del Centro de Cáncer, sin terapia preoperatoria. PRINCIPALES MEDIDAS DE RESULTADO: El resultado principal fue la supervivencia libre de recaídas. RESULTADOS: La mediana del período de seguimiento fue de 61, 7 meses (rango, 3-153 meses). Las tasas de supervivencia sin recaídas a cinco años, con margen de resección circunferencial predicho por resonancia magnética, en pacientes negativos y pacientes positivos fueron 76.0% y 55.6% ( p <0.001), respectivamente. Los análisis univariados y multivariados revelaron estadio pN (razón de riesgo [HR], 2.35; intervalo de confianza [IC] del 95%, 1.470-3.770; p <0.001), invasión linfática (HR, 2.03; IC del 95%, 1.302-3.176; p = 0.002), invasión venosa (HR, 2.15; IC 95%, 1.184-3.9; p = 0.01), procedimiento quirúrgico (HR, 1.72; IC 95%, 1.115-2.665; p = 0.01) y circunferencial predicho por resonancia magnética en margen de resección (HR, 1.850; IC 95%, 1.206-2.838; p = 0.0051), como factores de riesgo independientes, para la recurrencia postoperatoria. LIMITACIONES: Este estudio fue retrospectivo en diseño. CONCLUSIONES: El margen de resección circunferencial predicho de resonancia magnética, se asoció con una supervivencia libre de recaída sin terapia preoperatoria, lo que indica su potencial para uso en la selección de la terapia óptima preoperatoria. Consulte Video Resumen en http://links.lww.com/DCR/B335 .